Nickel–Iron Hydrogenases: High‐Resolution Crystallography Resolves the Hydride, but Not the Debate. Issue 12 (17th June 2015) - Schilter, David
<x xml:space="preserve">Abstract</x> An (X‐ray) eye for detail: Modern high‐resolution protein crystallography allows H atoms to be located. Applied to nickel–iron hydrogenase, X‐ray structural analysis has finally confirmed the presence of an active‐site hydride and thiol, as well as unveiling the intricate pathways that protons take to and from the active site.